A study on relationship between employability and career success among staff in DBKL / Nur Ain Azami - Azami, Nur Ain (2010)
This research is about the study on relationship between employability and career success among staff in DBKL. There are 3 elements under employability that influence career success which are knowledge, skill and ability. The survey is conducted at Kuala Lumpur City Hall (DBKL), Menara DBKL 3, Bandar Wawasan, Jalan Raja Abdullah, Kuala Lumpur. Sample size is about 60 respondents who are selected randomly. Data collection method that was used are primary and secondary data which is by questionnaire and through internet and journal as well. After data has been collected, the Statistical Package for the Social Science (SPSS)version 12.0 has been used to analyze the data. The result is in the form of reliability test, frequency, and correlation. From the result it shown that there are significance relationship between employability and career success however there are some elements under employability that are no relationship with career success which is knowledge. However, other than that, it is proven that there are relationship between skills and ability with career success. Besides that there are some recommendations in order to improve the employability level.